Soil Physicochemical Properties as Influenced by Land Use Practices in Ifite Ogwari, Anambra State (e-Proceedings of the Faculty of Agriculture International Conference, 2024)
Land use remains one of the major factors that can degrade soil properties with consequences on the provision of ecosystem services. This study was conducted at the faculty of Agriculture, Ifite Ogwari annex of Nnamdi Azikiwe University to investigate the influence of land use practices on selected physicochemical properties of soil. Three land use types (cassava farm, rice farm, grassland) with different histories were selected for the study. Soil samples were taken from each of the land use types in three replicates at 0-20cm and 20-40cm depths. To determine the physicochemical properties of soil under the land use types, samples were subjected to laboratory analysis. Data generated were subjected to statistical analysis and Duncan’s multiple range test was used to separate significant means at 5% probability level. The results showed a predominant clay textural class under the land use types. Highest soil bulk density and lowest total porosity was obtained under cassava farm with values of 1.94 g/cm3 and 30.31% respectively at 20-40cm depth. Soil hydraulic conductivity under the land use types ranged from 0.01- 0.03cm/hr. Aggregate stability of soils ranged from 0.32-0.56 across the depths. The silt clay ratio under land use types was generally low and showed a highly weathered soil. The soil pH was generally acidic. Soil organic carbon was generally low and ranged from 0.40-1.32% across the depths. The total nitrogen ranged from 0.01- 0.11% which was generally low across the depths. Available phosphorus was highest under cassava farm with a value of 8.33mg/kg at 0-20cm depth while grassland had the lowest available phosphorus content with a value of 0.86 mg/kg at 20-40cm depth. The cation exchange capacity under land use types ranged from 5.89 -8.65 cmol/kg at 0-20cm depth and 3.68 -7.55 cmol/kg at 20-40cm depth. It was generally observed that soil nutrients decreased as the depth increased. The studied land use types influenced the selected soil properties and this calls for soil conservation practices that could improve soil productivity.
Keywords: Agriculture; Conservation; Land-use types; Soil properties